The puzzling nuanced status of who free relative clauses in English: a follow-up to Patterson and Caponigro (2015) - Stockwell, R; Schütze, CT (Cambridge University Press, 2021)
This squib challenges Patterson & Caponigro's (2015, this journal) claim that there are few acceptable free relative clauses with who. We show that free relatives with who are generally acceptable when they are ‘transparent’ free relatives or complements of a copula, and add further nuance to their findings concerning how the degree of acceptability of free relatives with who varies according to positional factors.